JURIDICAL ANALYSIS OF ALLEGED CODE OF ETHICS VIOLATIONS AGAINST PRINCIPLES OF PROFESSIONALISM OF ELECTION ORGANIZERS - Handiki, Nabiel Purwa; Silfiyah, Silfiyah (Jurnal Abdisci, 2025)
Abstract Background. Elections are the central pillar in the democratic system, through the form of government, which actively involves all people in making authorized decisions. One of the codes of ethics includes basic principles such as professionalism. The principle of professionalism emphasizes competence, objectivity, efficiency, and adherence to the applicable set of rules. Aims. This study aims to analyze the alleged violation of the code of ethics against the principle of professionalism of election organizers according to Law No. 01 of 2015 concerning the Stipulation of Government Regulations instead of Law No. 1 of 2014 concerning the Election of Governors, Regents, and Mayors into Law. This research uses a normative approach and a study of legal documents and is related to the role and function of Bawaslu in election law enforcement. Methods. The types and sources of data used in this study are Primary Data, Secondary Data, DKPP Decisions, and relevant Literature. The case of losing 100 ballots at TPS 005, Karangsuwung Village, Karangsembung District, Cirebon Regency is an alleged violation of the code of ethics, professionalism, and integrity. Result. Conclusion. The analysis showed that violations of the code of ethics were sanctioned in the form of a written reprimand recommended to the Cirebon Regency KPU. Implementation.